Exposures to multiple air pollutants while commuting: Evidence from Zhengzhou, China. (15th February 2021) - deSouza, Priyanka; Lu, Ruiqing; Kinney, Patrick; Zheng, Siqi
Abstract: Daily commutes can contribute disproportionately to overall daily exposure to urban air pollutant concentrations. It is important to understand factors that contribute to the variability of exposures during commutes to develop strategies to mitigate exposure. We used low-cost Fairsense PMS1003 sensors to monitor exposure to multiple air pollutants: PM2.5, PM10, SO2, CO, O3 and NO2, across four dominant transport modes: bike, taxi, subway and bus, on prescribed commuting routes covering a wide range of environments representative of downtown Zhengzhou during the morning and evening rush hours. Zhengzhou is a city in China that faces severe air quality challenges. We compared exposures in the different modes and evaluated factors that contributed to variability in exposure to the different pollutants during commute trips. There were statistically significant differences in exposures across commuting modes for most pollutants. Commuting in air-conditioned taxis had the lowest exposure to PM, but highest exposures to some primary gaseous pollutants (SO2 and CO). In a multivariate analysis, the travel mode generally explained the greatest variability in pollutant exposure, in comparison to route, time of day (morning/evening), and background pollutant concentrations. When breathing rate was taken into account to compute pollutant doses, cycling emerged as the commuting mode with the highest inhaled dose. Graphical abstract: Image 1